Immunocytes Rapid Responses Post-ischemic Stroke in Peripheral Blood in Patients With Different Ages - Zhang, Haiyue; Guan, Jingwei; Lee, Hangil; Wu, Chuanjie; Dong, Kai; Liu, Zongjian; Cui, Lili; Song, Haiqing; Ding, Yuchuan; Meng, Ran (Frontiers in Neurology, 2022)
Objectives: To explore the alterations in immune cell composition in peripheral blood in patients with acute ischemic stroke (AIS) based on their age group. Methods: Patients with imaging confirmed AIS were enrolled from April 2019 to January 2020 and were divided into three groups according to their ages: < 55 years (group-A), 55-65 years (group-B), and > 65 years (group-C). Blood samples were collected immediately when the patients were admitted to our ward prior to any intervention. Flow cytometry was used to analyze immune cell composition in peripheral blood. Results: A total of 41 eligible patients were included for final analysis. Among the three groups, the proportions of CD56+ CD16dim NK cells were least to greatest in group-B, group-A, then group-C, respectively. With increasing age, there was a decrease in the proportion of CD3+ T-cells (group-A vs. group-C, P=0.016) and CD3+CD4+ T-cells (group-C vs. group-A, P=0.008; group-C vs. group-B P=0.026). Meanwhile, no significant differences in proportions of monocytes and B cells were observed. Conclusions: The compositions of immune cells in peripheral blood of AIS patients were distinct when divided by age groups. Differences in immune cell ratios may affect clinical outcomes and foreshadows possible need for customized treatment of AIS in different age groups.